Analysis of Motion Detection of Breast Tumor Based on Tissue Elasticity From B Mode Ultrasound Images Using Gradient Method Optical Flow Algorithm - Shuib, FMM; Abdulrahim, K; Zulkifli, Z; Marinah Othman (IEEE, 2024)
Date of Conference: 03-05 December 2013 Conference Location: Kota Kinabalu, Malaysia